Relationships of West Greenland supraglacial melt‐lakes with local climate and regional atmospheric circulation. (22nd August 2019) - Rowley, Nathan A.; Carleton, Andrew M.; Fegyveresi, John
Abstract: Along the west‐central Greenland ice sheet (GrIS) ablation zone, the time of annual maximum occurrence of surface melt‐lakes, or peak lake period (PLP) averages June 18–July 3. This study combines atmospheric reanalysis and automatic weather station data from the Greenland Climate Network to assess the roles of synoptic circulation patterns and local climate variables, respectively, in the total melt‐lake area and count in the Sermeq Kujalleq ablation region (SKAR) for the PLPs of 2000–2016. Melt‐lake information is obtained from analysis of Landsat‐7 images. Two surface climate parameters (e.g., temperature, incoming shortwave radiation) having a strong combined effect on melt‐lake area in the SKAR are the June mean temperature, and May mean incoming solar radiation ( r = .96). Incorporating the May insolation into a regression equation permits predictability of total melt‐lake area for the study area into late June. June months classified as high melt correlate regionally with mid‐tropospheric ridging, warm air advection, and reduced cloud cover, while low melt June months are associated with a trough, cold advection, and greater cloud amount. A localized feature that we found to be prevalent during the high‐melt years are piteraq, or downsloping winds, which provide additional warming to the SKAR from adiabatic compression. Atmospheric circulation indices comprising the North Atlantic Oscillation index (NAOI) teleconnection and Greenland blocking index (GBI) pattern augment the reanalysis gridded data. We find statistically significant correlations of the NAOI and GBI with melt‐lake area ( r = −.62 and r = .77, respectively). The correlations with melt‐lake count however, are not significant; greater combined lake area and count tend to accompany the meridional mode of high amplitude Rossby waves and/or anti‐cyclonic blocking in the Greenland sector. Determining the local and synoptic‐scale atmospheric controls on supraglacial lake variability helps clarify the role of climate in the surface hydrology of the GrIS. Abstract : A Landsat‐7 image (07 July, 2001) of the study area, known as the Sermeq Kajulleq ablation region, commonly referred to as the Jakobshavn ablation region, or JAR (within red box). The study area is north of the glacier (red dashed line) in west‐central Greenland. In the region surrounding the melt‐lakes is a linear transect of three automated weather stations, JAR‐2 (568 m), JAR‐1 (962 m), and Swiss Camp (1, 149 m) that are part of the Greenland Climate Network